Market variables influence customer behavior toward coffee business growth - Montajula Suvattanadilok (Cogent Business & Management, 2024)
This study investigates the impact of market engagement strategies—specifically market involvement, customer centricity, employee empowerment, and market innovation—on consumer behavior and business growth within the Thai coffee industry. Recognizing the pivotal role these factors play in shaping consumer preferences and fostering business expansion, this research aims to provide a comprehensive analysis of their influences.MethodologyEmploying a non-probability sampling method, data were collected from patrons of Thai coffee shops. Structural equation modeling was utilized to dissect the direct and indirect effects of market variables on consumer behavior and subsequent business growth, offering a detailed examination of the intricate dynamics at play.Key FindingsThe results underscore the significant contribution of market innovation and enhanced customer engagement in driving business growth. Specifically, this study analysis revealed that customer behavior serves as a critical mediator between market practices and business success, with employee empowerment and training emerging as key factors in promoting positive consumer experiences and sustaining growth.Contributions to the FieldThis research enriches the existing body of literature by delineating the integral role of market engagement strategies in the coffee sector, particularly within the Thai context. It elucidates the complex interplay between market initiatives and consumer behavior, providing empirical evidence of the pathways through which strategic market participation can catalyze business success. Furthermore, the study offers actionable insights for coffee companies seeking to navigate the competitive landscape through informed marketing strategies and business models, ultimately paving the way for long-term viability and success in the market.
Keywords: 650; Market engagement; customer centricity; employee liberty; market innovation; customer behavior; business growth; coffee industry